Towards practice change: a qualitative study examining the impact of a Child Psychiatric Access Program (Project TEACH) on Primary Care Provider practices in New York State during pandemic times - Nayla M. Khoury; Alex Cogswell; Melissa Arthur; Maureen Ryan; Eric MacMaster; David Kaye (BMC, 2023)
Abstract Background This study aims to explore the perceived impact of Project TEACH (Training and Education for the Advancement of Children's Health), a New York State Office of Mental Health funded Child Psychiatric Access Program (CPAP), on pediatric Primary Care Providers (PCPs) and their practice. Practice change over time was assessed in the context of rising mental health needs and in the context of COVID19 pandemic. Methods Focus groups utilizing a semi-structured format were conducted with pediatric PCPs who have been high utilizers of Project TEACH over the past 5-10 years and PCPs in similar regions who have been low or non-utilizers of the program. The semi-structured interview focused on practice change, asking about pediatric mental health, practice setting and flow, professional development, and changes over time in the context of COVID-19 pandemic and Project TEACH. Results Themes identified include increasing confidence of PCPs, particularly those who are high utilizers of the phone consultation line, increased routine use of screening and comfort bridging pediatric patients with mental health needs. Challenges include rising mental health needs, inadequate mental health services, difficulties with family follow through and high emotional burden on PCPs caring for these patients. In this context, participants noted that collaboration with Project TEACH provided needed emotional support. Conclusions Integrated care and CPAPs such as Project TEACH are vital to helping PCPs handle rising mental health needs particularly in current crisis times. Ongoing systemic challenges accessing care remain and contribute to emotional burden placed on pediatric PCPs.